Run away [compact disc, unabridged] - Coben, Harlan, 1962- (Brilliance Audio, 2018)
After discovering his drug-addicted daughter Paige, who he has not seen in six months, panhandling in Central Park, Simon follows her into a dark and dangerous world he never knew existed that puts his family and his life on the line.